2018
DOI: 10.1007/s11096-018-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Reporting adverse drug reactions: contribution, knowledge and perception of German pharmacy professionals

Abstract: Background The detection, assessment and prevention of adverse drug reactions along the product's life cycle is known as pharmacovigilance. German pharmacists are obliged by law to conduct pharmacovigilance measures, a specific training is not required. Objectives To assess the knowledge, contribution and perception of German pharmacy professionals regarding pharmacovigilance activities, in order to identify their needs to report better on the issue. Setting A semi-quantitative survey among German pharmacy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…24 Moreover, a German study in 2018 documented that although PV system was well-established and there were numerous reporting events in Germany, only 5-10% of serious ADRs and even lower percent of the non-serious ADRs were reported, and attributed that to the absence of mandatory continuing education programs for PV for German HCPs. 34 Practice scores showed significant improvement after education in the present work, and the number of ADRs reports increased from 2 to 13. All reported ADRs were done by pharmacists except for one that was reported by a nurse.…”
Section: Ta B L E 2 Comparison Of Kap Questionnaire Scores Of Hcps Between Groups and Within Groups In The Pre-and Post-education Phasesmentioning
confidence: 50%
“…24 Moreover, a German study in 2018 documented that although PV system was well-established and there were numerous reporting events in Germany, only 5-10% of serious ADRs and even lower percent of the non-serious ADRs were reported, and attributed that to the absence of mandatory continuing education programs for PV for German HCPs. 34 Practice scores showed significant improvement after education in the present work, and the number of ADRs reports increased from 2 to 13. All reported ADRs were done by pharmacists except for one that was reported by a nurse.…”
Section: Ta B L E 2 Comparison Of Kap Questionnaire Scores Of Hcps Between Groups and Within Groups In The Pre-and Post-education Phasesmentioning
confidence: 50%
“…Many studies included in this review lacked a theoretical framework. In papers in which a theoretical framework was utilized, Inmans’ seven deadly sins for not reporting ADEs; Knowledge‐Attitude‐Practice Model (KAP); and theory of planned behaviour were the most frequently used theories to understand pharmacists' reporting of ADEs …”
Section: Resultsmentioning
confidence: 99%
“…[24,[36][37][38] Many studies included in this review lacked a theoretical framework. In papers in which a theoretical framework was utilized, Inmans' seven deadly sins for not reporting ADEs [32,33,35,39,40] ; Knowledge-Attitude-Practice Model (KAP) [29][30][31]34,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] ; and theory of planned behaviour were the most frequently used theories to understand pharmacists' reporting of ADEs. [57] reporting [58] and knowledge [59] of ADEs in two studies.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…Previous studies have reported that although its overall impact was mild, training or educational seminars regarding pharmacovigilance improved the knowledge, attitudes, and practice of pharmacovigilance among various health care providers. 17,18 Laven et al 19 reported that the structured, mandatory training of a pharmacy team and the preparation of a standard operating procedure for a pharmacy or its integration with pharmacy software would lead to the successful integration of pharmacovigilance reporting in daily practice. Kitazawa et al 20 reported that pharmacoepidemiology, including pharmacovigilance, remains an immature field of study and that there are few appropriate textbooks and no teaching experts for pharmacoepidemiology.…”
Section: Discussionmentioning
confidence: 99%